2000
DOI: 10.1037/0033-295x.107.4.786
|View full text |Cite
|
Sign up to set email alerts
|

Individual and developmental differences in semantic priming: Empirical and computational support for a single-mechanism account of lexical processing.

Abstract: Existing accounts of single-word semantic priming phenomena incorporate multiple mechanisms, such as spreading activation, expectancy-based processes, and postlexical semantic matching. The authors provide empirical and computational support for a single-mechanism distributed network account. Previous studies have found greater semantic priming for low- than for high-frequency target words as well as inhibition following unrelated primes only at long stimulus-onset asynchronies (SOAs). A series of experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
438
6
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(474 citation statements)
references
References 223 publications
(409 reference statements)
15
438
6
5
Order By: Relevance
“…These properties emerge naturally in distributed connectionist models of lexical processing (e.g. Gaskell & Marslen-Wilson, 1997;Plaut & Booth, 2000;Plaut & Gonnerman, 2000;Seidenberg & Gonnerman, 2000), which view morphological relations as the simultaneous effect of similarity between distributed representations of form and meaning. In this respect, McKay (2003) indicates that information theory is indeed the apropriate tool for analyzing the behavior of a neuronal network.…”
Section: Discussionmentioning
confidence: 99%
“…These properties emerge naturally in distributed connectionist models of lexical processing (e.g. Gaskell & Marslen-Wilson, 1997;Plaut & Booth, 2000;Plaut & Gonnerman, 2000;Seidenberg & Gonnerman, 2000), which view morphological relations as the simultaneous effect of similarity between distributed representations of form and meaning. In this respect, McKay (2003) indicates that information theory is indeed the apropriate tool for analyzing the behavior of a neuronal network.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, phonological and orthographic representations become closely linked during reading acquisition. Behavioral and computational modeling research has shown that phonological and orthographic processes are more interactive in skilled versus less skilled readers (Booth, et al 1999;Plaut and Booth 2000). However, the neural mechanisms that underlie interactions between phonological and orthographic processes are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, some considerations can be drawn. In past years, autoassociative networks with attractor dynamics have frequently been used to explain priming (Kawamoto 1993;McRae and Boisvert 1998;Plaut and Booth 2000). A typical idea in these models is that a first object (the prime) which has some semantic similarity with a second object (the target) would place the network in a position of the state space close to the attractor of the target.…”
Section: Discussionmentioning
confidence: 99%